PENGUATAN UMKM SEBAGAI PENGGERAK PEMULIHAN EKONOMI KECAMATAN ALIAN KABUPATEN KEBUMEN - Prosawita Ririh Kusumasari; Ferryani Krisnawati; Eti Mul Erowati (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
The Covid-19 pandemic had a significant impact on the decline in the national and global economy. The third quarter of 2020 is an important and challenging momentum to restore the national economy. This legal counseling aims to provide understanding to students, parents, teachers, the elderly, people with disabilities and all other levels of society who act as implementers of Micro, Small and Medium Enterprises in the Alian District, Kebumen Regency, so as to gain an understanding of strengthening Micro, Small and Medium Enterprises as a driver of economic recovery. It is hoped that the community can participate in developing and maintaining what is good and realize that goodness in daily life wholeheartedly, becoming a habit that is continuously practiced and carried out every day. Hopefully people can get ease of understanding Micro, Small and Medium Enterprises implementers in Alian District, Kebumen Regency.